1986
DOI: 10.1002/qj.49711247417
|View full text |Cite
|
Sign up to set email alerts
|

Concerning the effect of surface drag on the circulation of a baroclinic planetary atmosphere

Abstract: Extended runs of a multi‐level spectral numerical model of atmospheric flow on a hemisphere have been used to investigate the effect of surface drag variations on the nature of the time‐averaged flow. It is shown that the most drastic effect of reducing the surface drag is to permit strong horizontal, barotropic shears in the zonal mean flow, which inhibit baroclinic instability. This superficially paradoxical result is implicit in many earlier calculations, most clearly in the lifecycle description of nonline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
77
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(83 citation statements)
references
References 32 publications
5
77
1
Order By: Relevance
“…At first glance, these results appear to directly support the barotropic governor mechanism, with increased drag causing the zonal mean winds to decrease, decreasing the barotropic shear and thus increasing the baroclinicity. However, one aspect of the response does not fit with previous work on the barotropic governor: globally averaged eddy kinetic energy decreases with increased drag [opposite to the increase found by James and Gray (1986)]. We therefore seek an alternative explanation for these effects of drag on the eddy fluxes.…”
Section: Introductioncontrasting
confidence: 49%
See 3 more Smart Citations
“…At first glance, these results appear to directly support the barotropic governor mechanism, with increased drag causing the zonal mean winds to decrease, decreasing the barotropic shear and thus increasing the baroclinicity. However, one aspect of the response does not fit with previous work on the barotropic governor: globally averaged eddy kinetic energy decreases with increased drag [opposite to the increase found by James and Gray (1986)]. We therefore seek an alternative explanation for these effects of drag on the eddy fluxes.…”
Section: Introductioncontrasting
confidence: 49%
“…Changes in heat flux therefore are likely not responsible for the lack of change of EKE. Many previous authors have used globally averaged EKE to diagnose the presence of the barotropic governor feedback between the eddies and the mean shear (James and Gray 1986;Robinson 1997;Chen et al 2007b), so the effect of drag on the EKE in the GEOS-5 model integrations suggests that perhaps a mechanism exists other than the conventional barotropic governor that explains this response of the eddies to drag.…”
Section: Motivation Frommentioning
confidence: 96%
See 2 more Smart Citations
“…He claims that the lateral scale of the Jovian and Saturnian zonal jets ͑and even that of the westerly jet seen in each hemisphere of the terrestrial atmosphere͒ is related to the Rhines scale. James and Gray 9 have argued, however, that the Williams model is only appropriate in situations where there is a large inertial range ͑for the inverse energy cascade͒ separating the baroclinic energy conversion scale ͑Rossby deformation radius͒ and L ␤ , which is not the case in the terrestrial atmosphere. 7 More recently Cho and Polvani 10 have performed a series of numerical simulations of freelyevolving shallow-water turbulence on a sphere, and found that although the number of jets increased with rotation rate as predicted by Rhines, the L ␤ scale could not be used as a quantitative predictor of that number.…”
Section: Introductionmentioning
confidence: 97%